Structural Properties and Interaction Partners of Familial ALS-Associated SOD1 Mutants - Huai, Jisen; Zhang, Zhongjian (Frontiers in Neurology, 2019)
Amyotrophic lateral sclerosis (ALS) is the most common motor neuron degenerative disease in adults and has also been proven to be a type of conformational disease associated with protein misfolding and dysfunction. To date, more than 150 distinct genes have been found to be associated with ALS, among which Superoxide Dismutase 1 (SOD1) is the first and the most extensively studied gene. It has been well established that SOD1 mutants-mediated toxicity is caused by a gain-of-function rather than the loss of the detoxifying activity of SOD1. Compared with the clear autosomal dominant inheritance of SOD1 mutants in ALS, the potential toxic mechanisms of SOD1 mutants in motor neurons remain incompletely understood. A large body of evidence has shown that SOD1 mutants may adopt a complex profile of conformations and interact with a wide range of client proteins. Here, in this review, we summarize the fundamental conformational properties and the gained interaction partners of the soluble forms of the SOD1 mutants which have been published in the past decades. Our goal is to find clues to the possible internal links between structural and functional anomalies of SOD1 mutants, as well as the relationships between their exposed epitopes and interaction partners, in order to help reveal and determine potential diagnostic and therapeutic targets